Associations of self-compassion with shame, guilt, and training motivation after sport-specific daily stress – a smartphone study. Issue 1 (2nd January 2023) - Röthlin, Philipp; Horvath, Stephan; Messerli, Tania; Krieger, Tobias; Berger, Thomas; Birrer, Daniel
ABSTRACT : By applying a diary study design, we investigated the role of self-compassion during sport-specific daily stress (SSDS) with regard to the negative self-conscious emotions of shame and guilt and training motivation. We hypothesised that self-compassion would protect athletes from certain self-conscious emotions, namely shame, after SSDS. We also predicted that self-compassion would either increase or decrease the relationship between stress and motivation. Ninety-six athletes ( Mage  = 22.14, SD  = 5.92) reported their level of self-compassion and evaluated their trainings and/or competitions over three weeks in terms of experienced stress, guilt, shame and subsequent training motivation on their smartphones. Multilevel analyses showed that SSDS was associated with more negative self-conscious emotions and reduced training motivation. Moreover, self-compassion weakened the effect of SSDS on shame and was not correlated with training motivation. We discuss the results with regard to sport psychology practice and future research.